2014
DOI: 10.2337/db13-1130
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Reduction of Plasma Free Fatty Acid Improves Mitochondrial Function and Whole-Body Insulin Sensitivity in Obese and Type 2 Diabetic Individuals

Abstract: Insulin resistance and dysregulation of free fatty acid (FFA) metabolism are core defects in type 2 diabetic (T2DM) and obese normal glucose tolerant (NGT) individuals. Impaired muscle mitochondrial function (reduced ATP synthesis) also has been described in insulin-resistant T2DM and obese subjects. We examined whether reduction in plasma FFA concentration with acipimox improved ATP synthesis rate and altered reactive oxygen species (ROS) production. Eleven NGT obese and 11 T2DM subjects received 1) OGTT, 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 27 publications
2
62
1
1
Order By: Relevance
“…Yet, lipid oversupply does not appear to further impair carbohydratesupported maximal coupled or uncoupled respiration within this cohort of subjects across a range of oxidative capacity. This is supported by the work of Daniele et al (11), who demonstrated that reducing circulating FFA levels increases carbohydrate supported ATP production in both type 2 diabetic patients as well as normal-glucose-tolerant subjects. We suggest that mitochondrial performance is not impaired to a greater degree in low-oxidative muscle confounded with obesity (14,23) within the context of excess lipid exposure.…”
Section: Discussionsupporting
confidence: 64%
“…Yet, lipid oversupply does not appear to further impair carbohydratesupported maximal coupled or uncoupled respiration within this cohort of subjects across a range of oxidative capacity. This is supported by the work of Daniele et al (11), who demonstrated that reducing circulating FFA levels increases carbohydrate supported ATP production in both type 2 diabetic patients as well as normal-glucose-tolerant subjects. We suggest that mitochondrial performance is not impaired to a greater degree in low-oxidative muscle confounded with obesity (14,23) within the context of excess lipid exposure.…”
Section: Discussionsupporting
confidence: 64%
“…Daniele et al (8) conclude that the mitochondrial defect in IR is partially reversible, which is consistent with other interventions, including weight loss and exercise, both of which also have profound effects on FFA metabolism and insulin sensitivity (17). However, this article used an intervention with specific direct FFA-lowering effects.…”
mentioning
confidence: 66%
“…Thus, it is possible that reductions in FFA have disparate effects on mitochondrial O 2 consumption and ATP production, both of which could result in an increased coupling. It is also likely that the longer-term treatment in the study by Daniele et al (8) had a fundamentally different effect on mitochondria. A deeper interrogation of mitochondrial respiratory states (e.g., basal, coupled and uncoupled respiration), in addition to ATP and H 2 O 2 measurements, could have revealed these potentially important effects of FFA reduction.…”
mentioning
confidence: 83%
“…The authors of this study also observed FFA rebound, occurring between acipimox doses, and pointed to this as the probable cause of the failure of long-term acipimox treatment to improve glycemia in the patients. A recent study confi rmed insulin sensitization in association with FFA lowering during short, intensive acipimox therapy, despite failure to reduce lipid accumulation in skeletal muscle ( 39 ). We hypothesize that to fully realize the potential of FFA lowering on improving glucose control, net FFA lowering must be achieved, and to do that the FFA rebound issue has to be solved (see below).…”
Section: Discussionmentioning
confidence: 99%